Plotagon Application Development Learning Speaking Skills - Adam Mudinillah; Nurfadilah; Septika Rudiamon (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2022)
The purpose of this study was to determine the role of the plotagon application in learning Arabic specifically speaking skills at MTs TI Canduang class VII. The object of this research is the seventh grade students of MTs TI Canduang. The research was conducted over several days with contributions from several educators at the school concerned. Of course, considering the development of technology as a form of world progress that still exists, the use of educational media is very necessary at this time. The Plotagon application, which can be used as a learning aid, proves that current technology not only has a negative impact on the world of education today, but also has a positive impact. The plotagon application is a program that is used online or designed, or it can also be called an editing application. For this reason, students can use the Plotagon application to help students learn Arabic, especially while learning to remember speaking skills. This application simplifies the work of educators, and researchers want students to be more enthusiastic about learning speaking skills. The results showed that the plotagon application was suitable for use as a medium for learning Arabic specifically for speaking skills.